Introduction: Organizational Discourses and Practices - IEDEMA, RICK and WODAK, RUTH (Discourse & Society, 1999)
This article provides a brief introduction to the other articles in this Special Issue, and sets out some of the traditions in linguistics and discourse analysis which have engaged in organizational research. The article then addresses some of the issues that define organizationality, such as impersonalization, power, and (re)production. The latter of these three is focused on in greater detail and is linked to current concerns with what is now termed the `recontextualization' of professional and organizational phenomena (Bernstein, 1990; Iedema, 1997a; Linell and Sarangi, 1998). Here, recontextualization is proposed to be at the heart of organizationality itself; that is, organizationality is seen as constituted in (re)productive processes which apply discipline/scientific technologies to human/exosomatic resources, producing lasting effects. These effects include both specialized practices and alternative social and material realities. Relatedly, we argue that organizational meaning making practices are to be considered as `multimodal' chains of recontextualization, with alternative semiotics such as design and built construction forming equally important links as does language in the chains of organizational processes.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wOTU3OTI2NTk5MDEwMDAxMDAx